The Effectiveness of Structured Pharmaceutical Education on Medication Adherence and Blood Pressure Control Among Hypertensive Patients at The Prafi Health Center - Baiq Suryaningsih (Universitas STRADA Indonesia, 2026)
Hypertension is a chronic disease with a high prevalence and is at risk of causing cardiovascular complications if not optimally controlled. One of the main factors of therapy failure is the patient's low adherence to taking antihypertensive drugs. Pharmaceutical personnel have a strategic role in improving compliance through structured education. This study aims to evaluate the effectiveness of structured pharmaceutical education on therapeutic adherence and blood pressure control in hypertensive patients at the Prafi Health Center, Manokwari.The study used a quasi-experimental design with a one-group pre-test and post-test approach in 48 hypertensive patients who met the inclusion criteria. The intervention was in the form of structured individual pharmacy counseling accompanied by educational leaflets. Measurements of adherence and blood pressure were taken before the intervention and four weeks after the intervention. The analysis used a paired t-test with a significance level of p < 0.05 and an effect size calculation (Cohen's d). The study used a quasi-experimental one-group pretest–posttest design involving 48 hypertensive patients who met the inclusion criteria. The sample was selected using a purposive sampling technique from patients who were diagnosed with hypertension, had received antihypertensive therapy for at least one month, and were willing to participate in the study.Medication adherence was measured using a self-report questionnaire consisting of eight statements with a four-point Likert scale (always, often, sometimes, never). The total score ranged from 0–24, where higher scores indicated better adherence. The reliability test showed good internal consistency (Cronbach’s alpha > 0.7).The decrease in blood pressure was not statistically significant.Structured pharmaceutical education was effective in improving medication adherence but did not demonstrate a significant change in blood pressure within the four-week observation period. This intervention has the potential to serve as a supportive strategy for hypertension management in primary healthcare settings.